FAIRS AND FESTIVALS AND SOCIAL DEVELOPMENT (International Journal of Food and Nutritional Sciences, 2022)
Fair and Festivals have direct and indirect impacts on communities. In Kanyakumari District, people become active agents of fair and festivals. They provide opportunities for participation, skills development, volunteering and social, cultural economic and environmental developments. Community events and festivals can attract tourists and visitors at regional, national and international level. Festivals help to capture attention and promote attractions and infrastructures. They make it possible to maximize and rationalize the use of certain spaces. Preservation of these spaces may result in financial benefits and dissemination of artistic and cultural heritages. Social benefits of festivals to communities can be extensive, particularly when the draw is from outside the region. Festivals and events have impacts that go well beyond what can be measured in economic terms. They contribute to the quality of life across Kanyakumari district by strengthening communities, providing unique activities and events, building awareness of diverse cultures and identities, and acting as a source of community pride.